Cálculo de la eficiencia de conducción y distribución en el Sector Hidráulico menor clase b del Rio Chonta y Cajamarquino en El Canal de Riego La Victoria, Yanamarca, Rumicucho – Cajamarca - Carranza Cordova, Galindo (2017)
This research work, describes the study for the calculation of the Conduct and Distribution Efficiency in the irrigation channel La Victoria, Yanamarca, Rumicucho in the district of Llacanora, Cajamarca, in addition to the improvements in the management of the water resource, with the purpose of allowing a greater number of irrigated areas with the same water supply. The data used in the present study were collected directly from the study areas that are: conduction channel and the respective distribution channels; other data necessary for the elaboration of this work have been provided by the Irrigation Users' Board of the Chonta River, ALA Cajamarca jurisdiction. The study includes the analysis of the conduction efficiency in the irrigation channel La Victoria and the analysis of the distribution efficiency in the irrigation channels Yanamarca and Rumicucho respectively. The flow rates of water made in the La Victoria channel (length 2.9 km) gives us a driving efficiency of 65.46%, the distribution channel Yanamarca L1 (length 1.2 km) has an efficiency of 76.46% and distribution channel Rumicucho L2 (length 2.4 km) has an efficiency of 59.33%, resulting in a distribution efficiency of 67.90%; as a consequence, the measurements made allow us to have a hydrometric record and at the same time these data obtained allow us to achieve greater efficiency in the programming, execution and evaluation of water management in the present irrigation channels. The lack of preventive and corrective maintenance in the studied channels and the application by means of traditional irrigation in the cultivated areas produces considerable losses of flows and as a consequence we have low efficiencies of conduction and distribution. Due to problems in the study channel, it is necessary to consider the management of the water resource, which assures us the coordinated management of water, land and related resources, with the objective of maximizing the economic and social well-being resulting in an equitable way.